2020
DOI: 10.1016/j.scitotenv.2020.139179
|View full text |Cite
|
Sign up to set email alerts
|

Assessing air quality changes in large cities during COVID-19 lockdowns: The impacts of traffic-free urban conditions in Almaty, Kazakhstan

Abstract: • PM 2.5 concentration reduced by 21% with spatial variations of 6-34% compared to the average of the same days in 2018-2019 • CO and NO 2 concentrations reduced by 49% and 35%, respectively • O 3 concentrations increased by 15% compared to the preceding 17 days before the lockdown • Concentrations of benzene and toluene were 2-3 times higher than in the same seasons of 2015-2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
331
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(403 citation statements)
references
References 11 publications
42
331
2
9
Order By: Relevance
“…Number of cities worldwide experienced air quality improvements during COVID-19 lockdowns; however, such changes may have been different in places with major contributions from nontra c related sources [14]. When we compared the concentration of PM 2.5 for 140 days before and 140 days during in Addis Ababa the mean concentration of PM 2.5 was increased 5.6 µg/m 3 during COVID-19 in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Number of cities worldwide experienced air quality improvements during COVID-19 lockdowns; however, such changes may have been different in places with major contributions from nontra c related sources [14]. When we compared the concentration of PM 2.5 for 140 days before and 140 days during in Addis Ababa the mean concentration of PM 2.5 was increased 5.6 µg/m 3 during COVID-19 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…People living in an area with high levels of pollutant are more prone to develop chronic respiratory conditions and suitable to any infective agent [13]. A number of cities worldwide experienced air quality improvements during COVID-19 lockdowns; however, such changes may have been different in places with major contributions from nontra c related sources [14].…”
Section: Introductionmentioning
confidence: 99%
“…But at the same time, some of them found that ozone increased distinctly. Similarly, (Kerimray et al 2020) indicated the concentrations of NO 2 , PM 2.5 , and CO reduced obviously.…”
Section: Introductionmentioning
confidence: 92%
“…Italy (Cristina et al 2020;Muhammad et al 2020;Zambrano-monserrate et al 2020), Spain, France (Muhammad et al 2020;Zambrano-monserrate et al 2020), USA (Muhammad et al 2020), Germany (Zambrano-monserrate et al 2020), Brazil (Dantas et al 2020), Kazakhstan (Kerimray et al 2020), etc.…”
Section: Introductionmentioning
confidence: 99%